2012
DOI: 10.2478/v10242-012-0013-z
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterization of human breast tissues by photoluminescence excitation-emission spectroscopy

Abstract: Fluorescence excitation-emission spectroscopy was used to investigate specimens of normal and malignant human breast tissues. Measurements were performed in two spectral regions: in the excitation range from 335nm to 400nm and emission range from 430nm to 625 nm, and in the excitation range from 400nm to 470nm and emission range from 500nm to 640 nm. It was found that fluorescence spectra are composed mainly of the emissions of extracellular proteins and that the differences in the intensity of their emissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Regarding breast cancer, it has been shown that distinct fluorescence response of tumors compared to one ordinary tissue is a result of notable differences in concentrations of collagen, elastin, NADH, and flavin adenine dinucleotide (FAD) [10]. Generally, fluorescence measurements have indicated lower concentrations of collagen and FAD and increased concentrations of NAD(P)H in malignant tissues compared to normal breast tissue [11]. Transformation from normal to malignant tissue leads to degradation and changes in the cross-links of collagen; breaking the cross-links in collagen is a consequence of the increased presence of collagenase in the tumor cells [12].…”
Section: Breast Tissue Fluorescencementioning
confidence: 99%
“…Regarding breast cancer, it has been shown that distinct fluorescence response of tumors compared to one ordinary tissue is a result of notable differences in concentrations of collagen, elastin, NADH, and flavin adenine dinucleotide (FAD) [10]. Generally, fluorescence measurements have indicated lower concentrations of collagen and FAD and increased concentrations of NAD(P)H in malignant tissues compared to normal breast tissue [11]. Transformation from normal to malignant tissue leads to degradation and changes in the cross-links of collagen; breaking the cross-links in collagen is a consequence of the increased presence of collagenase in the tumor cells [12].…”
Section: Breast Tissue Fluorescencementioning
confidence: 99%
“…Changes in the metabolic environment of cells (e.g., normal vs. cancer cells, changes after treatment) can be explored through the fluorescence spectra and abundance of fluorophores. Endogenous fluorophores including NADH, NADPH, FAD and porphyrins have generally been explored to analyse metabolic changes [24,25], whereas elastin [26] and collagen have been used to look at structural changes [27].…”
Section: Introductionmentioning
confidence: 99%
“…The changes in metabolism in cancerous and noncancerous tissue have been studied by analysing the fluorescence spectra of fluorophores [24,25]. NADH and FAD are the main coenzymes involved in cellular metabolism and are generally the predominate fluorescent signals present, thus are often used as metabolic markers [30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations